2013
DOI: 10.1007/s10637-013-9926-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study to assess the efficacy, safety and tolerability of the mitotic spindle kinesin inhibitor AZD4877 in patients with recurrent advanced urothelial cancer

Abstract: AZD4877 was generally tolerable in patients with advanced urothelial cancer. Given the limited clinical efficacy, further development of AZD4877 in urothelial cancer is not planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Moreover, it has been reported that KIF15 could assist cancer cells to develop chemotherapy resistance, thus affecting the efficiency of cancer treatment [45]. KIF15 tends to be compensatorily up-regulated when Eg5 is inhibited by anticancer drugs because of its structural and functional similarities to Eg5 in mitosis [46,47]. Therefore, whether KIF15 plays a role in chemotherapy of GC also needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that KIF15 could assist cancer cells to develop chemotherapy resistance, thus affecting the efficiency of cancer treatment [45]. KIF15 tends to be compensatorily up-regulated when Eg5 is inhibited by anticancer drugs because of its structural and functional similarities to Eg5 in mitosis [46,47]. Therefore, whether KIF15 plays a role in chemotherapy of GC also needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In most clinical trials with Eg5 inhibitors in which G-CSF support was not used, treatment durations were short which may have precluded demonstration of responses resulting from Eg5 inhibition. For example, in a recent Phase II trial of the Eg5 inhibitor AZD4877 in urothelial cancers(Jones et al, 2013), the median treatment duration was only 43 days (∼1.5 months) and no responses were noted. Since lowering neutropenia allowed higher doses, greater treatment duration and the demonstration of efficacy with ARRY-520, further lowering of neutropenia with the specific mode of Eg5 inhibition we identified (combined with G-CSF support) has the potential to improve further outcomes of patients treated with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Ispinesib, a KIF11targeted inhibitor, was the first KIF-inhibitor that was evaluated both safety and efficacy in breast cancer in phase I clinical study [30]. Other KIF-targeted drugs further tested in various cancers by clinical trials including KIF11 inhibitors (litronesib [31,32], filanesib [33][34][35], SB-743921 [36], AZD4877 [37]), KIF5C inhibitors (Lidocaine and Tetracaine [38]) and KIFC1 inhibitors (AZ82 and SR31527 [39,40]). However, limited efficacy was seen in all inhibitors reported.…”
mentioning
confidence: 99%